Effects of horizontal distance and limb crossing on perceived hand spacing and ownership: Differential sensory processing across hand configurations. Issue 1 (December 2018) - Qureshi, Hassan; Butler, Annie; Kerr, Graham; Gandevia, Simon; Héroux, Martin
Abstract We have previously shown that, with the hands apart vertically, passively grasping an artificial finger induces a sense of ownership over the artificial finger and coming-together of the hands. The present study investigated thisgrasp illusion in the horizontal plane. Thirty healthy participants were tested in two conditions (grasp andno grasp ) with their hands at different distances apart, either crossed or uncrossed. After 3 min, participants reported perceived spacing between index fingers, perceived index finger location, and, for thegrasp condition, perceived ownership over the artificial finger. On average, there was no ownership at any of the hand configurations. With the hands uncrossed 7.5, 15 or 24 cm apart, there was no difference in perceived spacing between thegrasp andno grasp conditions. With the hands crossed and 15 cm apart, perceived spacing between index fingers was 3.2 cm [0.7 to 5.7] (mean [95% CI]) smaller during thegrasp condition compared tono grasp . Therefore, compared to when the hands are vertically separated, there is an almost complete lack of a grasp illusion in the horizontal plane which indicates the brain may process sensory inputs from the hands differently based on whether the hands are horizontally or vertically apart.